ECONOMIC ANALYSIS OF ORANGE MARKETING IN GBOKO BENUE STATE, NIGERIA - Ochimana, G. A.; Atanu, M.; Kunya, M.T. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined economic analysis of orange marketing in Gboko, Benue State, Nigeria. A multi stage sampling procedure was used in selecting a sample of 120 respondents. Primary data were collected using a structured questionnaire and analyzed with descriptive statistics and benefit–cost ratio techniques. The results revealed that orange marketers were relatively young, with an average age of 34 years, and the trade was male-dominated (70%). Majority (65%) of respondents were married and lived in large households averaging seven persons. Education levels were fairly high, with 55% having secondary education, 30% having primary education, and 15% having tertiary education. Marketing experience was substantial, as 60% had over 10 years in the business. Income distribution showed that 45% earned less than ₦200,000 annually, 35% earned between ₦200,000 and ₦400,000, and 20% earned more than ₦400,000. Institutional participation was weak, with only 28% belonging to cooperatives, 22% accessing extension services, and 18% obtaining credit. Marketing channels were relatively direct: wholesalers supplied 55%, retailers handled 40%, while only 5% involved middlemen. Fresh oranges dominated sales (95%), with local markets absorbing 70% of total sales. The total cost incurred was ₦3,518,000, while total revenue reached ₦52,391,968, yielding a Benefit–Cost Ratio (BCR) of 14.89. Market structure analysis indicated that 69.17% perceived the system as monopolistic and 27.5% as perfectly competitive. Price uniformity was moderate for 51.67% of respondents, while access to market information was low for 54.17%. Market performance measures were favourable, with a Concentration Ratio (CR) of 7.29% and a Marketing Efficiency Index (MEI) of 27.91. Despite profitability, major constraints persisted. Price fluctuations (96.61%), pests and diseases (95.83%), high transportation costs (87.5%), poor road networks (83.33%), and unfavorable government policies (82.5%) were the most severe challenges. The study concludes that orange marketing in Gboko is highly profitable and efficient. Strengthening rural infrastructure, enhancing storage facilities, and expanding access to credit are recommended to improve the enterprise's sustainability.